The mtDNA control region structure and preliminary phylogenetic relationships of the genus Gampsocleis (Orthoptera: Tettigoniidae) - Zhang, Yan-Xia; Zhou, Zhi-Jun; Yang, Ming-Ru; Yang, Ming-Ru; Shi, Fu-Ming (Zootaxa, 2011)
The mitochondrial DNA control region (mtDNA CR) has been cloned and sequenced from 56 individuals representing five species of the genus Gampsocleis. The Neighbor-Joining (NJ) tree under the Kimura 2-parameter (K2P) model, G. sedakovii haplotypes cluster into two distinct clades A and B. It suggests there may be more than one species within this group. The macropterous species, G. sinensis grouped among G. ussuriensis. Two brachypterous species, G. carinata and G. gratiosa grouped as sibling species. Individuals of G. carinata and G. gratiosa grouped together in distinct clades, even when collected from different localities. MtDNA CR structural analysis found two conserved motifs in the primary sequences “(TA)n” and poly-A stretch in the twelve ensiferan species examined, which may be involved in mtDNA transcription or replication control.